Physiological response of goldsinny wrasse to global climate change ... : Fysiologisk respons hos stensnultra på globala klimatförändringar ... - Hammar Perry, Diana (Swedish University of Agricultural Sciences, 2024)
In order to understand the physiological effects of global climate change on goldsinny wrasse, a multi-stressor experiment was conducted exposing the fish to four weeks of experimental conditions with treatments consisting of control conditions (salinity approx 28, temp 13°C, pH approx 8.1), low salinity (17), high temperature (19°C), low ph (7.5) and the combination of all three stressors combined (multi-stressor treatment salinity 17, temp 19°C, and pH 7.5). Potential physiological stress was evaluated by measuring growth (weight and length), oxygen consumption using respirometry, and liver oxidative stress analyses (ratio GSSG-GSH, GSSG, GSH, CAT, GST, GR and LPO). Data from the Weight Length file contains information related to experimental treatment conditions, fish ID, and weight (g) and length (cm) at the end of the exposure period (4 columns, 123 rows). Data from the ratio GSSG-GSH, GSSG, GSH, CAT, GST, GR and LPO files are from enzymatic measurements of liver samples for oxidative stress analyses ... : Ett multi-stressorexperiment genomfördes för att bedöma det fysiologiska respons av stensnultra på globala klimatförändringsstressorer. En mer detaljerad beskrivning kan ses på engelska. ...